Amancio Isla Frez, La Crónica de Alfonso III y el reino astur, Gijón: Trea, 2019, 232 pp. ISBN: 978-84-17987-22-0. - Escudero Manzano, Gonzalo J. (De Medio Aevo, 2020)
Reseña del libro de Amancio Isla Frez, La Crónica de Alfonso III y el reino astur, Gijón: Trea, 2019, 232 pp. ISBN: 978-84-17987-22-0.